Mental health literacy and psychological outcomes in dual-career athletes - Usenik, J.; Kranjec, E. (Frontiers in Sports and Active Living, 2025)
Introduction: Dual-career athletes experience the unique challenges of balancing sporting, academic, and vocational pursuits, which can strain their well-being and increase psychological distress. This study examined the mental health of Slovenian dual-career athletes, including the prevalence of anxiety, depression, and overall well-being, as well as their mental health literacy and its potential relationship with psychological distress and well-being.